Development of Information Technology-Based Aqidah Akhlak Learning Strategy to Increase Learning Efficiency - Najamudin Najamudin; Surahman Hidayat; M. Ulil Albab (International Journal of Islamic Educational Research, 2024)
Learning strategies based on information technology are increasingly relevant in improving the efficiency of the educational process, including in the subject of Aqidah Akhlak. This study aims to develop an information technology-based learning strategy to improve the efficiency of Aqidah Akhlak learning in schools. With a descriptive qualitative approach and library research method, this research analyzes various literature related to the application of technology in Islamic education. The results show that the utilization of technology, such as digital media, online learning platforms, and interactive applications, can enrich the learning experience, facilitate access to learning resources, and increase student engagement. The proposed strategies include the integration of technology in learning planning, implementation of teaching and learning activities, and learning evaluation. This research provides recommendations for educators and educational institutions to optimize technology in Aqidah Akhlak learning.